Air transport management : an international perspective - Budd, Lucy; Budd, Lucy; Ison, Stephen (London ; New York, NY : Routledge, Taylor & Francis Group, 2020)
"Air Transport Management: An International Perspective provides in-depth instruction in the diverse and dynamic area of commercial air transport management. The 2nd edition has been extensively revised and updated to reflect the latest developments in the sector. The textbook includes both introductory reference material and more advanced content so as to provide a solid foundation in the core principles and practices of air transport management. This second edition includes a new chapter on airline regulation and deregulation and new dedicated chapters focusing on aviation safety and aviation security. Four new contributors bring additional insights and expertise to the book. The 2nd edition retains many of the key features of the 1st edition, including: A clearly structured topic-based approach that provides the reader with information on key air transport management issues including: aviation law, economics; airport and airline management; finance; environmental considerations, human resource management; and marketing; Chapters authored by leading air transport academics and practitioners worldwide provide an international perspective; Learning objectives and key points which provide a framework for learning; Boxed case studies and examples in each chapter; Keyword definitions and stop and think boxes are used to prompt reflection and aid understanding of key terms and concepts. Designed for undergraduate and postgraduate students studying aviation and business management degree programmes and industry practitioners seeking to expand their knowledge base, the book provides a single point of reference to the key legal, regulatory, strategic and operational concepts and processes that shape the form and function of the world's commercial air transport industry"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Airlines -- Management